Coronal Microleakage of the Resilon and Gutta-Percha Obturation Materials with Epiphany SE Sealer: An in-vitro Study - Arwa Ahmed Al-Maswary; Hatem Abdel-Hameed Alhadainy; Sadeq Ali Al-Maweri (Journal of Clinical and Diagnostic Research, 2016)
Introduction: The coronal leakage of bacteria and other irritants to the root canal system is one of the main factors that may result in clinical failure and affect the long term success of endodontic treatment. The Resilon/Epiphany obturation system has been developed as an alternative to gutta-percha and traditional sealers. Aim: This study aimed to evaluate and compare the coronal leakage between Resilon obturation material and gutta-percha using the same sealer. Materials and Methods: In this invitro study, 72 freshly extracted single-rooted human teeth were used, and were sectioned at CEJ with 13mm length. The roots were randomly divided into four groups. In Group I, 30 roots were obturated using Resilon and Epiphany SE sealer, Group II, 30 roots were obturated using gutta-percha and Epiphany SE. Group III and Group IV, 12 roots were used as control groups (positive and negative). The coronal leakage was measured using the dye penetration technique. Data were statistically analysed by a One-Way ANOVA test. Results: There was a significant difference between the two experimental groups where Resilon revealed less microleakage than gutta-percha group (p <0.05). Conclusion: Resilon is a suitable replacement for gutta-percha on the basis of its increased resistance to microleakage, but it failed to provide complete hermetic coronal sealing.